Gamification and Industry 4.0 : Gamified Smart Manufacturing - Konzack, Lars, 1969- (Routledge advances in production and operations management., 2025)
Gamification and Industry 4.0 are two concepts that each in their own right have sparked attention. Gamification as a way to use game elements in non-game activities, and Industry 4.0 as a way to describe how the interconnected digital transformation of operational technologies are changing manufacturing in the 21st Century. Gamification now offers an opportunity to enhance the productivity of manufacturing and improve quality of work life in the process. Gamification and Industry 4.0 looks at how the transformative shift of production and manufacturing opens up for gamified experiences in the work place. What the industry requires are deeper kinds of gamification, comprehending the knowledge of industrial production, computer applications, game design, learning, and motivational psychology. In order to achieve this, this book offers interdisciplinary expertise from such fields as psychology, management, software engineering, information science, game studies, and industrial production and innovation. The concept of Industry 4.0 and different types of gamifications are discussed in relation to motivation and learning. The book also examines cybersecurity of gamified systems and the potential risks any changes made to digital devices and industrial control systems may cause. This unique book will be of value to researchers, academics and upper-level students across various fields, but in particular, management and organization studies, production and manufacturing as well as technology and innovation management.